2021
DOI: 10.1111/sode.12514
|View full text |Cite
|
Sign up to set email alerts
|

Parental psychological control perceived in adolescence predicts jealousy toward romantic partners in emerging adulthood via insecure attachment

Abstract: Parental psychological control (PPC)'s association with romantic relationships and the mechanisms through which PPC impairs relationship qualities remain crucial questions to understanding PPC. To this end, we examine if insecure attachment at age 18 mediated the association between PPC perceived at age 16 and jealousy at age 22. Our results showed that PPC perceived at age 16 predicted attachment anxiety at age 18, which then predicted jealousy at age 22. Both mothers' and fathers' models show significant med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
1
5
1
Order By: Relevance
“…Our results can provide a starting point for identifying areas of children's development that fPC predicts. As recent work showed that mPC (compared with fPC) perceived in adolescence uniquely contributed to their later attachment anxiety and jealousy in their romantic relationships (Choe et al, 2021) We did not find a significant direct effect from PPC perceived at age 13 to physical aggression at age 18 in our mediation models, though significant direct paths from fPC to physical aggression exist in the models without the mediator.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…Our results can provide a starting point for identifying areas of children's development that fPC predicts. As recent work showed that mPC (compared with fPC) perceived in adolescence uniquely contributed to their later attachment anxiety and jealousy in their romantic relationships (Choe et al, 2021) We did not find a significant direct effect from PPC perceived at age 13 to physical aggression at age 18 in our mediation models, though significant direct paths from fPC to physical aggression exist in the models without the mediator.…”
Section: Discussioncontrasting
confidence: 74%
“…PPC has been argued to be universally detrimental to children's development (Soenens & Vansteenkiste, 2010). Consistently, several studies on PPC reported negative outcomes of PPC from both gender adolescents (e.g., Choe et al., 2020a; 2021). Hence examining the differences by the gender of adolescents can add to the literature: whether boys and girls develop differently after experiencing PPC or not and in which areas boys and girls present differences.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations